2014
DOI: 10.1071/sh13074
|View full text |Cite
|
Sign up to set email alerts
|

High rates of sexually transmissible infections in HIV-positive patients in the Australian HIV Observational Database: a prospective cohort study

Abstract: Background Sexually transmitted infections (STI) may directly increase the risk of HIV infection, or may indicate sexual practices that increase the risk of HIV infection. In persons with HIV they probably also increase the infectiousness of HIV, even in the context of treatment with antiretroviral drugs (ARV). Estimating STI in this group has proved problematic, and there are few longitudinal studies able to accurately measure incidence. Methods In 2010, we established a cohort of individuals from ten widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…We previously found a high incidence of STI diagnoses in the AHOD . Routine STI screening of HIV‐positive patients is recommended , and has been pretty universally implemented over the period from 2010 onwards – especially in the STI clinics included in this analysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We previously found a high incidence of STI diagnoses in the AHOD . Routine STI screening of HIV‐positive patients is recommended , and has been pretty universally implemented over the period from 2010 onwards – especially in the STI clinics included in this analysis.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are limitations to our study design. First, although our sample is representative of the parent cohort , the latter may not be representative of the general population with HIV infection. Secondly, although the pharynx accounted for only 7% of known site diagnoses, this does not necessarily mean that oral transmission is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Known risk factors for STIs include sexual behaviour history (eg, sex without condoms, casual sex partners, sexualised drug use), current use of PrEP, and HIV-positive status. [12][13][14] A recent analysis of clinical data from Boston, United States, explored the effectiveness of different doxy-PEP prescribing strategies to prevent one case of bacterial STI. 15 This analysis found that prescribing doxy-PEP for 12 months to individuals with one or more recent STI diagnosis (within the previous 12 months) was an efficient strategy for reducing the amount of doxy-PEP prescribed, with the number needed to treat (NNT) ranging from 1.3 to 1.5 to prevent one bacterial STI case over 12 months.…”
mentioning
confidence: 99%
“…Known risk factors for STIs include sexual behaviour history (eg, sex without condoms, casual sex partners, sexualised drug use), current use of PrEP, and HIV‐positive status 12‐14 . A recent analysis of clinical data from Boston, United States, explored the effectiveness of different doxy‐PEP prescribing strategies to prevent one case of bacterial STI 15 .…”
mentioning
confidence: 99%